A comparative evaluation of fracture resistance of teeth restored with inlay and direct composite resin techniques - Sayed Mostafa Mousavinasab; Tayebeh Mansouri (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Composite resin restorations have the advantage of restoring the strength of lost tooth structures, which is affected by the technique in which composite resins are used. The aim of this in vitro study was to compare the effect of two restorative techniques with composite resin and enamel and dentin bonding agents on fracture resistance of restored teeth.Materials and Methods: In the present in vitro study fifty extracted human maxillary premolars were divided into five groups, mounted in acrylic resin and restored as follows after MOD cavities were prepared: group 1: composite resin inlay restoration; group 2: unprepared teeth as controls; group 3: etched enamel and direct composite resin restoration with enamel bonding agents; group 4: prepared but un-restored teeth; group 5: etched enamel, DBA application and composite resin restoration. The samples were prepared and subjected to a compressive force. Data was analyzed using one-way ANOVA; t-test was used for two-by-two comparisons (α = 0.05).Results: The mean fracture resistance values in kgf and standard deviations were 87 (23.16), 142 (53.77), 60.87 (11.52), 41.12 (12.08) and 91.5 (23.60) in groups 1, 2, 3, 4, and 5, respectively, with statistically significant differences between groups 2, 3 and 4 (p value < 0.05). There were no significant differences between groups 1 and 5 (p value > 0.05).Conclusion: The results showed that prepared but un-restored teeth were less fracture resistant than restored teeth. No significant differences were noted in fracture resistance between teeth restored with composite inlay (group 1) and etching the enamel and application of DBA and composite resin (group 5), although both techniques increased fracture resistance. Restoration of prepared teeth with bonded composite resin increased fracture resistance. Key words: Composite resins, Dental bonding, Inlays.